FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS TIDUR PADA REMAJA DI SMKN 7 PEKANBARU - Dewi Setia Ningsih; Rani Indah Permatasari (Ensiklopedia of Journal, 2020)
Sleep of basic of health and the growth and adult. Nowdays there are some adult that have less of sleep quality for adult that have less of sleep quality and irregular sleep schedule can cause be sleepy un the day, bad mood, bad achievement and increase risk of accident. The purpose of this research to knows the factors that influence quality of sleep for adult in SMKN 7 Pekanbaru. This research has population amount of 421 people with total sample 81 people. The kind of this research is quantitive with cross sectional design and the methods to take of sample is purposive sampling. Questionnaire is the measuring instrument with used chi-square tes. The result of this research show of there is no connectivity between life style with quality of sleep with p value = 0,779 > α = 0,05. There is connecticity environmental with quality of sleep wit p value = 0,013 < α= 0,05. There is connectivity psychology stress with quality of sleep with p value 0,007 < α= 0,05. Hopefuly students can manage their activity schedule so they can get regular sleep schedule and as source of information all about factors that influence quality of sleep.